Looking for information : examining research on how people engage with information - Given, Lisa M. (Studies in information., 2023)
This fifth edition of Looking for Information is redesigned to reflect the breadth of research across information behaviour studies, with a new streamlined, six-chapter structure, presenting a refreshed look at people's information needs and seeking practices, while also embracing contemporary concepts such as information use, creation, and embodiment. This edition retains its core purpose by highlighting essential aspects of research on people's information behaviours, including detailed examples from more than 1200 research publications. The authors present historic works (including those focused on people's occupations) alongside contemporary research addressing the situations and contexts that shape people's experiences. Studies using innovative methodological or theoretical approaches, and those reflecting ongoing shifts towards interdisciplinarity are also featured. The authors carefully balance quick access to summaries and highlights, alongside long-form narratives, while retaining the content and focus that readers of Looking for Information have come to expect. Each chapter serves as a stand-alone piece of writing, with its own reference list and Must-Read recommendations, facilitating e-reading and inclusion on course syllabi. All these features will enhance readers' experiences of this new edition.